2012
DOI: 10.18697/ajfand.53.10775
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of fast food consumption in Kampala, Uganda

Abstract: Consumption of fast-food in Uganda is becoming an increasingly important component of the food market as more of the working class choose to dine out rather than prepare meals at home. Despite the importance of the fast-food sector, limited attempts have been made to study the consumption and expenditure behaviour of consumers of fast-food in Uganda. The main objective of this study was to assess characteristics influencing the consumption of fast-food in Kampala district. Specifically, the objectives of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…These factors have previously been identified among college students (4). Having holiday job was an independent predictor found in this study which is not unconnected to possible availability of disposable income, suggest some level of independence and increased likelihood to spend more time away from home or hostel (21). Similarly, the earlier years of the study was found to predict frequent fast food consumption.…”
Section: Discussionsupporting
confidence: 60%
“…These factors have previously been identified among college students (4). Having holiday job was an independent predictor found in this study which is not unconnected to possible availability of disposable income, suggest some level of independence and increased likelihood to spend more time away from home or hostel (21). Similarly, the earlier years of the study was found to predict frequent fast food consumption.…”
Section: Discussionsupporting
confidence: 60%
“…When socioeconomic levels increase, kiosks provide the main source of away-from-home foods [ 36 ]. On the other hand, fast food establishments like Nando’s, Domino’s pizza, and Steers are mostly preferred by the working class in Uganda [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…EAFH is becoming increasingly popular in Uganda due to changing demographic trends. In particular, the working class now prefer EAFH to eating at home [ 6 ]. The prevalence of EAFH has been reported to be 39.2% in Uganda, and reportedly, 69.5% of men and 30.5% of women eat ≥ 3 meals away from home per week [ 7 ], which underscores the importance of this eating behavior in Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in income in middle-class families and in the influences of urbanisation encourages dietary diversification, including increased consumption of animal products, sugars, fats and processed foods. As urbanisation intensifies and the middle-class population expands, there is a likelihood that a significant proportion of the population will be driven to consume unhealthy fast foods, changing the country's nutritional profile and placing burdens on the health sector (Ayo et al, 2012). Fast food is seen as an easy solution to consumers' busy schedules and limited meal preparation times that are the result of urban lifestyles.…”
Section: Shift In Dietary Patternsmentioning
confidence: 99%
“…However, the share spent on ultra-processed food increases with rising income and is higher for urban households (26%) than rural households (14%). The major motivations for consuming fast-food are taste, convenience and relatively short preparation time (Ayo et al, 2012).…”
Section: Consumptionmentioning
confidence: 99%